Analysis of H2S-related short-term degradation and regeneration of anode- and electrolyte supported solid oxide fuel cells fueled with biomass steam gasifier product gas. (1st March 2021) - Pongratz, G.; Subotić, V.; Schroettner, H.; Hochenauer, C.; Skrzypkiewicz, M.; Kupecki, Jakub; Anca-Couce, A.; Scharler, R.
Abstract: Using solid oxide fuel cells in biomass gasification based combined heat and power production is a promising option to increase electrical efficiency of the system. For an economically viable design of gas cleaning units, fuel cell modules and further development of suitable degradation detection methods, information about the behavior of commercially available cell designs during short-term poisoning with H2 S can be crucial. This work presents short-term degradation and regeneration analyses of industrial-relevant cell designs with different anode structure and sulfur tolerance fueled with synthetic product gas from wood steam gasification containing 1 to 10 ppmv of H2 S at 750°C and 800°C. Full performance regeneration of both cell types was achieved in all operating points. The high H2 O content and avoided fuel depletion may have contributed to a lower performance degradation and better regeneration of the cells. A strong influence of the catalytically active anode volume on poisoning and regeneration behavior was quantified, thereby outlining the importance of considering the anode structure besides the sulfur tolerance of the anode material. Hence, cells with less sulfur tolerant anode material but larger anode volume might outperform cells less sensitive to sulfur in the case of an early detection of a gas cleaning malfunction. Highlights: H2 S degradation and regeneration of commercially available solid oxide fuel cells. Operating conditions relevant for coupling of cells with biomass gasifiers. Full regeneration achieved even at 750°C and 10 ppmv H2 S poisoning for both cells. High water content in fuel might decrease degradation and improve regeneration. Anode structure important for sulfur degradation and regeneration.